Common Fixed-Point Results in Ordered Left (Right) Quasi-b-Metric Spaces and Applications - Hemant Kumar Nashine; Sourav Shil; Hiranmoy Garai; Lakshmi Kanta Dey; Vahid Parvaneh (Journal of Mathematics)
We use the notions of left- and right-complete quasi-b-metric spaces and partial ordered sets to obtain a couple of common fixed-point results for strictly weakly isotone increasing mappings and relatively weakly increasing mappings, which satisfy a pair of almost generalized contractive conditions. To illustrate our results, throughout the paper, we give several relevant examples. Further, we use our results to establish sufficient conditions for existence and uniqueness of solution of a system of nonlinear matrix equations and a pair of fractional differential equations. Finally, we provide a nontrivial example to validate the sufficient conditions for nonlinear matrix equations with numerical approximations.